STUDI KASUS: ASUHAN KEBIDANAN KOMPREHENSIF PADA NY.H UMUR 28 TAHUN MULTIGRAVIDA DI PUSKESMAS GARUNG KABUPATEN WONOSOBO - Pradesti, Oktavia Dwi; Nugraheni, Nazilla; Romdiyah, Romdiyah; Inayah, Wilda (Jurnal Ilmiah Kesehatan, 2024)
The Indonesian government continues to strive to reduce the maternal mortality rate (MMR) and infant mortality rate (IMR) in Indonesia, which are still relatively high. One of the efforts taken is to improve midwifery care with the SOAP method comprehensively (Continuity of Care). The goal is to provide comprehensive or continuous midwifery care. The subject taken was Mrs. H, 28 years old. Assessment was carried out from March 08 to April 22, 2024. From the results of pregnancy assessment carried out 2 times and found high risk in Mrs. H, namely chronic energy deficiency (CED) and pregnancy with too close a distance. Maternity care found complications, namely retensio placenta. Immediate care of newborns and neonates 4 times there were no complications. Postpartum care was carried out 4 times and there were no complications. Family planning care uses the 1 stem implant method and no complications were found. The conclusion of this assessment is that there is a gap between theory and practice regarding the implementation of Early Breastfeeding Initiation. Suggestions from the assessment that the improvement of midwifery services continues to be carried out to improve early detection and prevention of complications.